1983
DOI: 10.2134/jeq1983.00472425001200010002x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Algal‐available Phosphorus on Soil and Sediment: A Review and Analysis

Abstract: Important advances have been made recently in identifying the sources of algal‐available P in soils and sediments. Algal bioassays have shown that considerable amounts of the total soil P may be algal‐available under the appropriate environmental conditions. At present, however, the reported research contains no convincing evidence that the bioassay techniques used quantitatively measured all of the algal‐available P present in the soils and sediments tested,. Although chemical fractionation procedures have sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The amount of phosphate available to algae from sediments has been assessed by means of bioassays, which are cultures of algae with sediment as the only source of phosphate (Golterman, 1969 ;Hegemann et al, 1983 ;Klapwijk, 1982) .…”
Section: Resultsmentioning
confidence: 99%
“…The amount of phosphate available to algae from sediments has been assessed by means of bioassays, which are cultures of algae with sediment as the only source of phosphate (Golterman, 1969 ;Hegemann et al, 1983 ;Klapwijk, 1982) .…”
Section: Resultsmentioning
confidence: 99%
“…The differences in SS concentrations can be explained by greater flow rates during storm flow than base flow: flow rate and SS erosion are usually correlated. Similarly, since P is tightly sorbed to sediment (Hegemann et al 1983), TP concentration can be expected to increase with flow rate. Elevated TP concentrations can also induce DRP enrichment of flowing water provided P is desorbed in proportion to TP concentration.…”
Section: Contaminant Concentration and Load In Flowmentioning
confidence: 99%
“…However, many authors have shown that 20 to 80% of PP (particulate phosphorus) may be available for algae if most of PP is inorganic, e.g. incorporated into clay particles (see Golterman et al, 1969;Williams et al, 1980;Young & De Pinto, 1982;Hegemann et al, 1983). Grobbelaar (1983) showed that more than 80% of the acid-labile phosphorus adsorbed to suspended solids may be available for algae.…”
Section: Introductionmentioning
confidence: 99%